The Archaeology of Late Antique 'Paganism'. - Lavan, Luke.
1 online resource (709 pages)
Keywords: There is no agreement over how to name the 'pagan' cults of late antiquity. Clearly they were more diverse than this Christian label suggests, but also exhibited tendencies towards monotheism and internal changes which makes it difficult to describe them as 'traditional cults'. This volume, which includes two extensive bibliographic essays, considers the decline of urban temples alongside the varying evolution of other focii of cult practice and identity. The papers reveal great regional diversity in the development of late antique paganism, and suggest that the time has come to abandon a single compelling narrative of 'the end of the temples' based on legal sources and literary accounts. Although temple destructions are attested, in some regions the end of paganism was both gradual and untraumatic, with more co-existence with Christianity than one might have expected. Contributors are Javier Arce, Béatrice Caseau, Georgios Deligiannakis, Koen Demarsin, Jitse H.F. Dijkstra, Demetrios Eliopoulos, James Gerrard, Penelope J. Goodman, David Gwynn, Luke Lavan, Michael Mulryan, Helen G. Saradi, Eberhard W. Sauer, Gareth Sears, Peter Talloen, Peter Van Nuffelen and Lies Vercauteren.